The cat, the collector and the killer - Sweeney, Leann (Sweeney, Leann. Cats in trouble mystery., 2016)
Jillian Hart and police chief Tom Stewart are enjoying peaceful newly wedded bliss in Mercy, South Carolina, until a woman is found wandering the streets one night. She's in her nightclothes, disoriented, and carrying a kitten in a tote bag. A search of the woman's house reveals many more cats, a maze of cardboard boxes--and a dead man. Although the evidence suggests the frail woman is the killer, Jillian doesn't believe she's capable of such a crime. The dead man had many enemies in town, which means finding the real murderer may prove to be its own cat-and-mouse game.